Reduced diversity of intestinal T-cell receptor repertoire in patients with Crohn’s disease - Hong, Sung Noh; Park, Joo-Young; Yang, So-Yun; Lee, Chansu; Kim, Young-Ho; Joung, Je-Gun (Frontiers in Cellular and Infection Microbiology, 2022)
Background The intestinal microenvironment directly determines the human T-cell receptor (TCR) repertoire. Despite its extreme diversity, TCR repertoire analysis may provide a better understanding of the immune system in patients with inflammatory bowel disease. Methods To investigate TCR repertoires in the intestinal mucosa, RNA sequencing was performed for inflamed and non-inflamed intestinal mucosa samples obtained from 13 patients with Crohn’s disease (CD) and healthy mucosa from nine non-IBD controls. Results The gene expression frequency of the TCR repertoire showed a clear separation between inflamed mucosa of patients with CD and healthy mucosa of non-IBD controls in the hierarchical clustering heatmap. The richness of TCR repertoires measured by the Chao1 index did not show a significant difference among groups, whereas diversity measured by the D50 diversity index was decreased in the inflamed mucosa of CD patients. Rare/small TCR clonotypes occupied a large proportion of TCR repertoires in healthy mucosa of controls, whereas expanded clonotypes were common in inflamed mucosa of patients with CD. Segment usages of TRAV2, TRAV22, TRAV40, TRJ14, TRAJ51, TRBV1, TRBV21.1, and TRBJ1.5 were significantly decreased in CD patients. KEGG enrichment analysis identified the enrichment of several KEGG pathways, including inflammatory bowel disease (p = 0.0012), Th1 and Th2 cell differentiation (p = 0.0011), and intestinal immune network for IgA production (p = 0.0468). Conclusions The diversity of the TCR repertoire is reduced in inflamed mucosa of CD patients, which might contribute to intestinal inflammation.